1998
DOI: 10.1016/s1059-1311(98)80073-3
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive effects of anticonvulsant monotherapy in elderly patients: a placebo-controlled study

Abstract: Old age is recognized to be the commonest time in life to develop epilepsy. There is a perception that older patients are more sensitive to the deleterious cognitive effects of antiepileptic drugs (AEDs). Elderly patients (median age 70 years, range 60-88 years) taking anticonvulsant monotherapy (10 carbamazepine [CBZ], 8 sodium valproate [VPA], 5 phenytoin [PHT]) took an extra dose of their usual medication (200mg CBZ, 500mg VPA, 100mg PHT) and matched placebo each for a month in random order. The concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…The cognitive side effects of AEDs do not develop only at higher doses: there is indeed no significant correlation between dose and cognitive impairment for PHT in a large cohort study (19) and nor for VPA (20,21). This is in accordance with the finding that, generally, side effects of VPA are not related to dose or serum level (22).…”
Section: The Cognitive Effects Of Commonly Used Drugssupporting
confidence: 77%
“…The cognitive side effects of AEDs do not develop only at higher doses: there is indeed no significant correlation between dose and cognitive impairment for PHT in a large cohort study (19) and nor for VPA (20,21). This is in accordance with the finding that, generally, side effects of VPA are not related to dose or serum level (22).…”
Section: The Cognitive Effects Of Commonly Used Drugssupporting
confidence: 77%
“…The central aim of this study was to examine differential cognitive effects of GBP and CBZ. Previous attention to potential neuropsychological effects of AEDs in seniors has been limited and has compared only more traditional AEDs (4,11). This study demonstrated that for the 11 cognitive variables, only a single measure of attention was statistically different between the two AEDs.…”
Section: Discussionmentioning
confidence: 73%
“…Sparse effort has been directed to the study of the potential cognitive effects of CBZ in senior adults despite its widespread clinical use for chronic seizures and other conditions. Read et al (11) recently found no significant changes in various cognitive task performances in senior adults who took an extra dose of their AED medication (either CBZ, VPA, or PHT). They concluded that cognitive impairment does not develop when modest dose increases are given in patients taking therapeutic monotherapy AED.…”
mentioning
confidence: 99%
“…Most of the published sources extrapolate treatment recommendations from experience in the general epilepsy population, either refer to retrospective case series pooled from different studies, or limit data to pharmacokinetics, drug exposure and/or tolerability (1,(9)(10)(11)(12)(13)(14)(15)(16). Trials for registration purposes often exclude elderly patients.…”
mentioning
confidence: 99%